Seasonal variations in the gut bacteriome of Apis mellifera assessed through 16S rRNA gene sequencing - M. Yasmeen; M. Hussain; F. Imran; R. Amjad; G. Mustafa; K. Ali; H. Rafiq; H. Fatima (Regulatory Mechanisms in Biosystems, 2025)
Honeybees play a crucial role in global food production and ecosystem maintenance through pollination, yet their health is increasingly threatened by environmental stresses, including changes in diet and climate. The present study investigates the seasonal variations in the gut bacteriome of Apis mellifera using 16S rRNA gene sequencing to unde r stand how microbial diversity fluctuates across different seasons. Worker bees were sampled from five colonies during spring and winter at the University of Veterinary and Animal Sciences, Pattoki, Pakistan. DNA was extracted from pooled gut samples and high-throughput sequencing was performed using universal 16S rRNA primers targeting the V3-V4 region. The results revealed that Proteobacteria dominated the gut microbiome in both seasons accounting for 74.4% in winter and 76.2% in spring. However, spring samples exhibited a richer and more balanced bacterial comm u nity with a higher Shannon diversity index (1.904 vs. 1.814) and Fisher index (1.296 vs. 1.117) compared to winter. At the genus level, Commensalibacter was the most abundant in both seasons but with higher prevalence in spring (37.0%) compared to winter (30.2%). Other key genera included Gilliamella , Pseudomonas and Bifidobacterium , which are essential for nutrient processing and immune defense. Seasonal shifts likely reflect changes in available floral r e sources, temperature, and beekeeping practices such as sugar supplementation during winter. These findings highlight the importance of a diverse gut microbiome in honeybee health and suggest that targeted interventions, such as probiotic supplementation and dietary management, could help maintain microbial balance throughout the year and improve colony resilience in varying environmental conditions.